2019
DOI: 10.1101/790584
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mindfulness meditation alters neural activity underpinning working memory during tactile distraction

Abstract: Evidence suggests that mindfulness meditation (MM) improves selective attention and reduces distractibility by enhancing top-down neural modulation. Altered P300 and alpha neural activity from MM have been identified and may reflect the neural changes that underpin these improvements. Given the proposed role of alpha activity in supressing processing of task-irrelevant information, it is theorised that altered alpha activity may underlie increased availability of neural resources in meditators. The present stu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 90 publications
(95 reference statements)
2
5
0
Order By: Relevance
“…More frontal distributions of the P3 have also been found in our previous research in meditators (N. W. Bailey et al, 2019; Wang et al, 2019), and we have previously suggested these alterations reflect enhanced attention.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…More frontal distributions of the P3 have also been found in our previous research in meditators (N. W. Bailey et al, 2019; Wang et al, 2019), and we have previously suggested these alterations reflect enhanced attention.…”
Section: Discussionsupporting
confidence: 85%
“…Our research has also demonstrated reduced overall neural response strength concurrent with increased behavioural performance in meditators (N. W. Bailey et al, 2019; Wang et al, 2019).…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations